PENGARUH SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION (STUDI KASUS LAYANAN AFTER SALES SERVICE ASTRA DAIHATSU CABANG SETIABUDI BANDUNG) - Jabir, Muh. Agung; Dewi, Citra Kusuma (JURNAL ILMIAH EDUNOMIKA, 2024)
Along with the number of sales and research on consumers, Astra Daihatsu also compensates with innovation and quality improvement from before consumers buy products to after sales services. The primary objective of the company is to optimize customer satisfaction. This research endeavors to examine the extent of the impact of service quality on customer satisfaction within the after-sales service context at the Astra Daihatsu Setiabudi Bandung branch. The data for this research was gathered through the distribution of questionnaires, employing a quantitative data analysis approach within the framework of descriptive-causal research. Sampling was conducted using a non-probability sampling method, specifically employing the purposive sampling technique. There were 245 samples used and analysed with multiple linear regression. The research revealed that when considered collectively (simultaneously), service quality dimensions such as tangibles, reliability, responsiveness, assurance, and empathy exhibited a positive and substantial impact on customer satisfaction. However, when analyzed individually (partially), it was observed that only assurance and empathy demonstrated a significant influence, whereas tangibles, reliability, and responsiveness did not exhibit a significant effect on customer satisfaction. Keywords: Tangibles, Reliability, Responsiveness, Assurance, Empathy.